Cash Waqf Linked Sukuk: overcoming social disparities in Indonesia - Ana Naila Rochaniah; Fita Nurotul Faizah (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
Indonesia faces persistent socioeconomic inequalities in healthcare, education, and economic participation despite its high human development potential, exacerbated by fiscal constraints limiting government-led solutions. This article examines the role of Cash Waqf Linked Sukuk (CWLS) –an innovative Islamic social finance instrument– in addressing these disparities by analyzing its implementation challenges and sectoral impacts. Using a qualitative case study approach with secondary data from government reports, regulatory documents, and national statistics, the research reveals that CWLS has successfully funded healthcare infrastructure (e.g., retina and glaucoma centers), educational scholarships, and agricultural empowerment programs. However, its potential remains underutilized due to low public trust, regional participation imbalances, and misalignment with critical needs such as cancer treatment facilities, rural school infrastructure, and tourism-based economic development. The study contributes to policy and practice by proposing three interventions: (1) targeted CWLS yield distribution to high-impact sectors, (2) enhanced transparency and nazhir (waqf manager) competency, and (3) public awareness campaigns to broaden participation. These findings offer a model for Muslim-majority countries seeking to leverage Islamic finance for equitable development.